2021
DOI: 10.1002/jcla.24169
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy ATG16L1 rs2241880 impacts the colorectal cancer risk: A case‐control study

Abstract: Background Despite many efforts to discover the important role of the autophagy process in the pathogenesis of colorectal cancer (CRC), the exact involved molecular mechanism still remains to be elucidated. Recently, a limited number of studies have been employed to discover the impact of autophagy genes’ variants on the development and progression of CRC. Here, we evaluated the association between two single‐nucleotide polymorphisms (SNPs) in the main components of the autophagy genes, ATG16L1 rs2241880, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Studies have revealed that polymorphisms in the ATG5 promoter such as rs510432 and rs506027 and ATG16L1 (rs2241880) play a role in various immune-mediated, malignancies, or infectious diseases [42,[44][45][46][47][48]. According to the effects of these polymorphisms on the expression of ATGs [49], we examined the association of these genetic variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that polymorphisms in the ATG5 promoter such as rs510432 and rs506027 and ATG16L1 (rs2241880) play a role in various immune-mediated, malignancies, or infectious diseases [42,[44][45][46][47][48]. According to the effects of these polymorphisms on the expression of ATGs [49], we examined the association of these genetic variations.…”
Section: Discussionmentioning
confidence: 99%
“…ATG genes polymorphism can play a role as an element in pathogenesis of different diseases [42,48,49]. In one study, it has been determined that ATG16L1 rs2241880 polymorphisms are related to colorectal cancer risk [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the primary stages of neoplasia formation, autophagy plays a tumor-suppressive role to maintain normal homeostasis inside the cells. In later stages of cancer formation, autophagy could induce tumor growth, which is the second role of autophagy in carcinogenesis [ 10 ]. The autophagy process is mediated through autophagy-related proteins (ATG).…”
Section: Introductionmentioning
confidence: 99%
“…The autophagy process is mediated through autophagy-related proteins (ATG). Several studies have shown that the SNPs in ATG genes may be correlated with the risk of many cancers such as melanoma, gastric cancer, colorectal cancer, and HCC [ 10 , 11 ]. The ATG16L1 gene which is located on chromosome 2 plays a vital role in autophagy.…”
Section: Introductionmentioning
confidence: 99%